Seeing Inscriptions on the Shroud of Turin: The Role of Psychological Influences in the Perception of Writing - Jordan, Timothy R.; Sheen, Mercedes; Abedipour, Lily; Paterson, Kevin B. (PLOS ONE, 2015)
The Shroud of Turin (hereafter the Shroud) is one of the most widely known and widely studied artifacts in existence, with enormous historical and religious significance. For years, the Shroud has inspired worldwide interest in images on its fabric which appear to be of the body and face of a man executed in a manner consistent with crucifixion, and many believe that these images were formed in the Shroud’s fibers during the Resurrection of Jesus of Nazareth. But, more recently, other reports have suggested that the Shroud also contains evidence of inscriptions, and these reports have been used to add crucial support to the view that the Shroud is the burial cloth of Jesus. Unfortunately, these reports of inscriptions are based on marks that are barely visible on the Shroud, even when images are enhanced, and the actual existence of writing on the Shroud is still a matter of considerable debate. Here we discuss previous evidence concerning the psychological processes involved generally in the perception of writing, and especially when letters and words are indistinct. We then report two experiments in which the influence of religious context on perception of inscriptions was addressed specifically, using an image of woven fabric (modern linen) containing no writing and with no religious provenance. This image was viewed in two different contexts: in the Religious Context, participants were informed that the image was of a linen artifact that was important to the Christian faith whereas, in the non-religious Neutral Context, participants were informed that the image was of a simple piece of linen. Both groups were told that the image may contain faint words and were asked to report any words they could see. All participants detected words on the image, and indicated that these words were visible and were able to trace on the image the words they detected. In each experiment, more religious words were detected in the Religious Context condition than in the Neutral Context condition whereas the two contexts showed no effect on the number of non-religious words detected, indicating that religious context had a specific effect on the perception of illusory writing. Indeed, in the Neutral Context condition, no religious words at all were reported in either experiment. These findings suggest that images of woven material, like linen, inspire illusory perceptions of writing and that the nature of these perceptions is influenced considerably by the religious expectations of observers. As a consequence, the normal psychological processes underlying perception of writing, and the tendency of these processes to produce illusory perceptions, should be an essential consideration when addressing the existence of religious inscriptions on religious artifacts such as the Shroud of Turin.